Method for preparing gasoline from plastic
By using a catalyst containing active components of tungsten, zirconium, aluminum or niobium, combined with mesoporous and microporous molecular sieves, the dependence problem on precious metals and co-reactants in the prior art is solved, and efficient plastic conversion and improvement of gasoline yield is achieved.
Patent Information
- Application Number
- CN202411560760.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2024-10-23
- Filing Date
- 2024-11-04
- Publication Date
- 2025-02-28
AI Technical Summary
The prior art relies heavily on organometallic complexes, precious metal catalysts, co-reactants or complex downstream treatments when converting waste plastics into valuable products, increasing the difficulty and cost of treatment and potentially leading to environmental pollution.
A method of preparing gasoline using plastics is adopted. The catalyst used includes active components such as tungsten, zirconium, aluminum or niobium, and uses mesoporous molecular sieve as a support and a microporous silicon-aluminum molecular sieve as a second catalyst to carry out a catalytic cracking reaction, avoiding dependence on precious metals and co-reactants.
It significantly enhances the conversion effect of polyolefin plastics, improves the plastic conversion rate and gasoline yield, and the catalyst is stable in the air, easy to synthesize, and the reaction conditions are mild, reducing coke formation, and the catalyst can be reused multiple times.
Smart Images

Figure CN119529870A_ABST
Abstract
Description
[0001] CROSS-REFERENCE TO RELATED APPLICATIONS
[0002] This application claims the benefit of Chinese patent application 202411485451.9 filed on October 23, 2024, the contents of which are incorporated herein by reference. Technical Field
[0003] The invention relates to the technical field of plastic resource utilization, and in particular to a method for preparing gasoline by utilizing plastic. Background Art
[0004] Plastics are one of the most commonly used functional polymer materials and are used in almost all industrial and commercial fields. As of 2017, global plastic production has soared to 8.3 billion tons and is expected to exceed 34 billion tons by 2050. Polyolefins account for about 25% of global plastic production. Because they are polymers with CC bonds as their backbone, they are difficult to degrade in the environment, resulting in large accumulations of polyolefin waste in landfills and natural environments, posing a threat to various ecosystems. Although burning polyolefins can recover energy, it releases a large amount of carbon dioxide. Pyrolysis and catalytic pyrolysis catalyze the degradation of polyolefin plastics under high temperature conditions (>400°C), but the high energy input catalytic reaction usually leads to the non-selective breaking of CC bonds of polyolefin plastics, generating complex products and coke that require cumbersome separation steps, resulting in catalyst deactivation. Hydrogenolysis is a method that efficiently breaks the CC single bonds of polyolefins under milder conditions (<300°C), but it is prone to excessive hydrogenolysis, resulting in the generation of C1-C3 hydrocarbons of a large number of light compounds. In addition, the use of high-pressure hydrogen poses safety risks and increases equipment investment and operating costs.
[0005] In recent years, some methods for degrading polyolefins under milder conditions (<300°C) have emerged, compared with pyrolysis and catalytic pyrolysis to directly break CC single bonds. Degradation methods under mild conditions first activate the CH bonds of polyethylene (414 kJ / mol), and then convert CC single bonds into olefin C=C double bonds, thereby promoting the catalytic breakage of polymer chains. In an ionic liquid environment, tert-butyl chloride can effectively activate the CH bonds in polyethylene (PE) to generate carbon cations. The activated PE carbon cations can be rapidly depolymerized and converted to C4-C by isomerization, breakage, and alkylation with isopentane. 36 Alkanes. Organometallic zirconium catalysts activate the CH bonds of PE through a σ bond exchange reaction, which then undergoes β-alkyl elimination to form oligomers with C=C double bonds. These oligomers undergo heterobimetallic alkyl exchange with AlR3 to form aliphatic alkylaluminum intermediates, which are then oxidized to fatty acids or alcohols. Precious metal iridium complexes, platinum and ruthenium-based catalysts can also activate the CH bonds of polyolefins, allowing unsaturated polyolefins to be further converted to olefins, aromatics or C4-C12 Alkane.
[0006] However, these above low-temperature conversion polyethylene degradation strategies heavily rely on organometallic complexes (which are sensitive to air and water), noble metal catalysts, co-reactants (such as hydrogen and solvents), or complex downstream processing. Therefore, there is an urgent need to develop cost-effective, efficient and robust catalytic systems for converting waste plastics into valuable products. Summary of the invention
[0007] The purpose of the present invention is to overcome the problems in the prior art that waste plastics are heavily dependent on organic metal complexes, precious metal catalysts, co-reactants or complex downstream processing in converting them into valuable products, which increases the difficulty and cost of processing and easily causes environmental pollution. A method for preparing gasoline using plastics is provided. The catalyst used in the technical solution can exist stably in the air and is cheap and easy to synthesize. It does not require the participation of co-reactants such as hydrogen, solvents or olefins, and at the same time significantly enhances the conversion effect of polyolefin plastics.
[0008] In order to achieve the above-mentioned purpose, the present invention provides a method for preparing gasoline using plastics, the method comprising: in an inert atmosphere, subjecting polyolefin plastics to a catalytic cracking reaction under the action of a first catalyst and a second catalyst, wherein the first catalyst contains an active component and an optional carrier, the active component is at least one of a tungsten component, a zirconium component, an aluminum component and a niobium component, and the carrier is a mesoporous molecular sieve; the second catalyst is a microporous silicon-aluminum molecular sieve; the mass ratio of the first catalyst to the second catalyst is 1:(0.25-20).
[0009] Preferably, the mass ratio of the first catalyst to the second catalyst is 1:(0.25-4).
[0010] Preferably, the mass ratio of the total mass of the first catalyst and the second catalyst to the amount of the polyolefin plastic used is (0.1-1):1.
[0011] Preferably, the polyolefin plastic is polyethylene plastic and / or polypropylene plastic.
[0012] Preferably, the ratio of the average pore diameter of the first catalyst to that of the second catalyst is (1.75-3.2):1.
[0013] Preferably, in the first catalyst, the mesoporous molecular sieve is at least one of KIT-6, MCM-41 and SBA-15.
[0014] Preferably, the first catalyst contains an active component and a carrier, and the mass proportion of the active component in the first catalyst is 1.15%-62.59%.
[0015] Preferably, the first catalyst contains an active component and a carrier, the active component is a tungsten component and a zirconium component, and the carrier is KIT-6.
[0016] Preferably, the mass proportion of the active component in the first catalyst is 8.3%-51.62%, preferably 11%-39%, more preferably 16%-32%.
[0017] Preferably, the mass ratio of the tungsten component to the zirconium component is 1:(0.08-4).
[0018] Preferably, the method further comprises preparing the first catalyst according to the following steps: mixing and stirring a tungsten source, a zirconium source, a silicon source, a template, hydrochloric acid, n-butanol and water, followed by a hydrothermal reaction to obtain a mixture, separating a solid phase from the mixture and calcining the mixture.
[0019] Preferably, the tungsten source is ammonium metatungstate and / or tungsten chloride.
[0020] Preferably, the zirconium source is at least one of zirconium oxychloride, zirconium chloride, zirconium nitrate and zirconium sulfate.
[0021] Preferably, the silicon source is ethyl silicate and / or methyl silicate.
[0022] Preferably, the template is P123 and / or F127.
[0023] Preferably, the ratio of the amount of the tungsten source, the zirconium source, the silicon source, the template, the hydrochloric acid, the n-butanol and the water is (0.2-1.8) g: (0.4-1.8) g: (6-10) g: (3.5-4) g: (5-8) g: (3.5-4) g: 130 mL.
[0024] Preferably, the concentration of the hydrochloric acid is 30wt%-38wt%.
[0025] Preferably, the conditions of the hydrothermal reaction include: temperature of 90-110° C. and time of 20-30 h.
[0026] Preferably, the calcination conditions include: temperature of 550-750° C. and time of 5-8 h.
[0027] Preferably, the second catalyst is at least one of β molecular sieve, Mordenite molecular sieve, MCM-22 molecular sieve and HZSM-5 molecular sieve, preferably HZSM-5 molecular sieve.
[0028] Preferably, the conditions for the catalytic cracking reaction include: a temperature of 220-280° C. and a time of 1-48 h.
[0029] Preferably, the catalytic cracking reaction is carried out in a tank reactor.
[0030] Compared with the prior art, the present invention has the following technical effects:
[0031] (1) In the method for preparing gasoline from plastics described in the present invention, the long chain of polyolefin is pre-broken under the action of the first catalyst to generate short-chain polymer substances with unsaturated carbon-carbon double bonds, which can not only increase the mass transfer and heat transfer efficiency of the reaction, but also further generate gasoline-range hydrocarbons through hydrogen transfer, β-cracking and aromatization reactions under the action of the second catalyst at low temperature. Through the synergistic effect of the first catalyst and the second catalyst, the conversion effect of polyolefin plastics is significantly enhanced, the plastic conversion rate and gasoline yield are improved, and the maximum yield of gasoline-range hydrocarbons reaches 88% under the condition of 240°C;
[0032] (2) The first catalyst and the second catalyst of the present invention can stably exist in the air and are cheap and easy to synthesize. They can catalyze the degradation of polyolefin plastics at low temperature without the need for precious metals and co-reactants such as hydrogen, solvents and olefins. At the same time, compared with a single catalyst system, the synergistic effect of the first catalyst and the second catalyst significantly enhances the conversion effect of polyolefin plastics.
[0033] (3) The first catalyst and the second catalyst of the present invention have adjustable structures and suitable acid sites, which not only utilize the contact between the plastic degradation process and the catalytic active sites to increase the mass transfer and heat transfer efficiency, but also improve the selectivity of gasoline products, reduce the amount of small molecular C1-C3 alkanes generated, and improve the octane number of gasoline;
[0034] (4) The method for preparing gasoline from plastics described in the present invention has mild reaction conditions, is not easy to produce coke, and the catalyst can still maintain its initial performance after multiple reactions and recycling. BRIEF DESCRIPTION OF THE DRAWINGS
[0035] Figure 1 is a TEM image of WZr-KIT-6 prepared in Example 1;
[0036] Figure 2 is a TEM image of the HZSM-5 molecular sieve in the embodiment;
[0037] Figure 3 are XRD patterns of WZr-KIT-6, HZSM-5, and a mixture of WZr-KIT-6 and HZSM-5 prepared in Example 1;
[0038] Figure 4is a low temperature nitrogen adsorption-desorption curve diagram of WZr-KIT-6, HZSM-5 and a mixture of WZr-KIT-6 and HZSM-5 prepared in Example 1;
[0039] Figure 5 is ammonia TPD graph of WZr-KIT-6, HZSM-5 and a mixture of WZr-KIT-6 and HZSM-5 prepared in Example 1;
[0040] Figure 6 : is the catalytic cycle diagram of WZr-KIT-6 and HZSM-5 prepared in Example 1. DETAILED DESCRIPTION
[0041] The specific embodiments of the present invention are described in detail below. It should be understood that the specific embodiments described herein are only used to illustrate and explain the present invention, and are not used to limit the present invention.
[0042] The endpoints and any values of the ranges disclosed in this article are not limited to the precise ranges or values, and these ranges or values should be understood to include values close to these ranges or values. For numerical ranges, the endpoint values of each range, the endpoint values of each range and the individual point values, and the individual point values can be combined with each other to obtain one or more new numerical ranges, which should be considered as specifically disclosed in this article.
[0043] The method for preparing gasoline from plastics of the present invention comprises: in an inert atmosphere, catalytic cracking reaction of polyolefin plastics under the action of a first catalyst and a second catalyst, wherein the first catalyst contains an active component and an optional carrier, the active component is at least one of a tungsten component, a zirconium component, an aluminum component and a niobium component, and the carrier is a mesoporous molecular sieve; the second catalyst is a microporous silicon-aluminum molecular sieve; the mass ratio of the first catalyst to the second catalyst is 1: (0.25-20). According to the method of the present invention, the synergistic effect of the first catalyst and the second catalyst not only facilitates the contact between the plastic degradation process and the catalytic active sites, increases the mass transfer and heat transfer efficiency, but also greatly improves the selectivity of the gasoline product; and the first catalyst and the second catalyst can stably exist in the air and are cheap and easy to synthesize, and do not require precious metals and co-reactants such as hydrogen, solvents and olefins, and catalyze the degradation of polyolefin plastics at low temperature.
[0044] In the method described in the present invention, in order to enhance the conversion effect of polyolefin plastics, the mass ratio of the first catalyst to the second catalyst is preferably 1:(0.25-4), more preferably 1:(2-4), for example, 1:0.25, 1:0.5, 1:1, 1:2, 1:3 or 1:4.
[0045] In the method described in the present invention, in order to increase the contact between the polyolefin plastic and the catalytic active sites and improve the mass transfer and heat transfer efficiency, the mass ratio of the total mass of the first catalyst and the second catalyst to the amount of the polyolefin plastic is preferably (0.1-1):1, more preferably (0.25-0.5):1, and specifically can be 1:4, 2:7, 1:3, 2:5 or 1:2.
[0046] In the method of the present invention, the polyolefin plastic may be polyethylene plastic and / or polypropylene plastic, preferably polyethylene plastic. The weight average molecular weight of the polyethylene plastic may be 40,000-100,000. The weight average molecular weight of the polypropylene plastic may be 80,000-100,000. Both the polyethylene plastic and the polypropylene plastic may be commercially available.
[0047] In the method of the present invention, in order to improve the plastic conversion rate and gasoline yield, the average pore size ratio of the first catalyst to the second catalyst is preferably (1.75-3.2):1, more preferably (1.8-2.4):1. The average pore size of the first catalyst can be 4.2-7.7nm, preferably 3.6-4.8nm; the specific surface area can be 460-700m 2 / g, preferably 460-600m 2 / g. The average pore size of the second catalyst may be 2-2.4 nm, preferably 2-2.2 nm; the specific surface area may be 300-400 m 2 / g, preferably 350-400m 2 / g.
[0048] In the method of the present invention, in order to improve the selectivity of gasoline products, in the first catalyst, the mesoporous molecular sieve is preferably at least one of KIT-6, MCM-41 and SBA-15, and more preferably KIT-6. The first catalyst may contain an active component and a carrier, and the mass proportion of the active component in the first catalyst may be 1.15%-62.59%, preferably 16%-32%. In some embodiments, the first catalyst contains an active component and a carrier, the active component is a tungsten component and a zirconium component, the carrier is KIT-6, the mass proportion of the active component in the first catalyst is 8.3%-51.62%, and the mass ratio of the tungsten component to the zirconium component is 1: (0.08-4). In other embodiments, the first catalyst contains an active component and a carrier, the active component is a tungsten component, the carrier is KIT-6, and the mass proportion of the active component in the first catalyst is 8.3%-51.62%. In other embodiments, the first catalyst contains an active component and a carrier, the active component is a zirconium component, the carrier is KIT-6, and the mass proportion of the active component in the first catalyst is 8.3%-51.62%. In other embodiments, the first catalyst contains an active component and a carrier, the active component is an aluminum component, the carrier is MCM-41, and the mass proportion of the active component in the first catalyst is 1.15%-3%. In other embodiments, the first catalyst contains an active component and a carrier, the active component is an aluminum component, the carrier is SBA-15, and the mass proportion of the active component in the first catalyst is 1.77%-54%. In other embodiments, the first catalyst contains an active component and a carrier, the active component is a niobium component and an aluminum component, the carrier is SBA-15, the mass proportion of the active component in the first catalyst is 5.8%-62.59%, and the mass ratio of the niobium component to the aluminum component is 1: (0.14-12.48). In other embodiments, the first catalyst contains active components, the active components are zirconium components and aluminum components, and the mass ratio of the zirconium component to the aluminum component is 1: (0.14-0.3). In other embodiments, the first catalyst contains active components, the active components are tungsten components and aluminum components, and the mass ratio of the tungsten component to the aluminum component is 1: (3.82-13.39).
[0049] In the method of the present invention, when the first catalyst contains an active component and a carrier, the active component is a tungsten component and a zirconium component, and the carrier is KIT-6, the mass proportion of the active component in the first catalyst can be 8.3%-51.62%, preferably 11%-39%, and more preferably 16%-32%; the mass ratio of the tungsten component to the zirconium component can be 1:(0.08-4), preferably 1:(0.2-4), and more preferably 1:(0.4-3.6). The method can also include preparing the first catalyst according to the following steps: mixing and stirring a tungsten source, a zirconium source, a silicon source, a template, hydrochloric acid, n-butanol and water, and then performing a hydrothermal reaction to obtain a mixture, separating a solid phase from the mixture and calcining. The tungsten source can be ammonium metatungstate and / or tungsten chloride, preferably ammonium metatungstate. The zirconium source can be at least one of zirconium oxychloride, zirconium chloride, zirconium nitrate and zirconium sulfate, preferably zirconium oxychloride. The silicon source can be ethyl silicate and / or methyl silicate, preferably ethyl silicate. The template may be P123 (polyethylene oxide-polypropylene oxide-polyethylene oxide triblock copolymer) and / or F127 (polyethylene glycol-polypropylene glycol-polyethylene glycol triblock copolymer), preferably P123. The ratio of the amount of the tungsten source, the zirconium source, the silicon source, the template, the hydrochloric acid, the n-butanol and the water may be (0.2-1.8) g: (0.4-1.8) g: (6-10) g: (3.5-4) g: (5-8) g: (3.5-4) g: 130 mL, preferably (0.7-1) g: (0.7-1) g: (7-9) g: (3.6-3.8) g: (5-7) g: (3.6-3.8) g: 130 mL. The concentration of the hydrochloric acid may be 30 wt%-38 wt%, preferably 36 wt%-38 wt%.
[0050] In the method of the present invention, the stirring conditions include: the temperature can be 20-30°C, preferably 23-28°C; the stirring rate can be 400-800rpm, preferably 500-700rpm; the time can be 20-30h, preferably 22-26h.
[0051] In the method of the present invention, the conditions of the hydrothermal reaction include: the temperature can be 90-110° C., preferably 95-105° C.; the time can be 20-30 h, preferably 22-26 h.
[0052] In the method of the present invention, the specific process of separating the solid phase from the mixture may include: separating the solid phase from the mixture by filtration and washing and drying. The drying conditions include: the temperature may be 100-120°C, preferably 105-115°C; the time may be 20-30h, preferably 22-26h.
[0053] In the method of the present invention, the calcination conditions include: the temperature can be 550-750° C., preferably 550-650° C.; the time can be 5-8 hours, preferably 6-7 hours. The calcination is carried out in a muffle furnace.
[0054] In the method of the present invention, when the first catalyst contains an active component and a carrier, the active component is an aluminum component, and the carrier is SBA-15, the mass proportion of the active component in the first catalyst is 1.77%-54%. The method may also include preparing the first catalyst according to the following steps: mixing P123, oxalic acid and a first hydrochloric acid, then mixing with ethyl silicate, stirring at 20-30°C with a stirring rate of 400-800rpm for 20-30h to obtain SBA-15; then placing the prepared SBA-15 in an aqueous solution of aluminum nitrate, and adjusting the pH to 1.5-2.5 by a second hydrochloric acid, then placing in a closed autoclave, hydrothermally reacting at 110-130°C for 20-30h, separating the solid phase from the obtained mixture by filtration, washing and drying at 100-120°C for 20-30h to obtain Al-SBA-15. The concentration of the first hydrochloric acid may be 1-3mol / L. The amount ratio of the P123, the oxalic acid, the first hydrochloric acid and the ethyl silicate can be (2-3) g: (1-1.5) g: 40 mL: (4-5) g. The concentration of the aluminum nitrate aqueous solution can be 0.1-3 mol / L. The amount ratio of the SBA-15 and the aluminum nitrate aqueous solution can be (0.8-1.5) g: 10 mL. The concentration of the second hydrochloric acid can be 0.5-2 mol / L.
[0055] In the method described in the present invention, when the first catalyst contains an active component and a carrier, the active component is a niobium component and an aluminum component, and the carrier is SBA-15, the mass ratio of the active component in the first catalyst is 5.8%-62.59%, and the mass ratio of the niobium component to the aluminum component is 1:(0.14-12.48). The method may also include preparing the first catalyst according to the following steps: mixing P123, a first oxalic acid and a first hydrochloric acid, and then mixing with ethyl silicate, stirring at 20-30°C at a stirring rate of 400-800rpm for 20-30h to obtain SBA-15; then placing the prepared SBA-15 in an aqueous solution of aluminum nitrate, and adjusting the pH to 1.5-2.5 by a second hydrochloric acid, and then placing it in a closed autoclave, performing a hydrothermal reaction at 110-130°C for 20-30h, and filtering the obtained mixture. The solid phase is separated from the mixture, washed and dried at 100-120°C for 20-30h to obtain Al-SBA-15 (the active component is the aluminum component and the carrier is SBA-15); Al-SBA-15, niobic acid, the second oxalic acid and water are mixed and stirred at 20-30°C with a stirring rate of 400-800rpm for 14-20h, the solid phase is separated from the obtained mixture by filtration, washed and dried at 100-120°C for 20-30h, and then calcined at 400-550°C for 5-8h. The concentration of the first hydrochloric acid can be 1-3mol / L. The amount ratio of the P123, the first oxalic acid, the first hydrochloric acid and the ethyl silicate can be (2-3)g: (1-1.5)g: 40mL: (4-5)g. The concentration of the aluminum nitrate aqueous solution can be 0.1-3mol / L. The usage ratio of the SBA-15 and the aluminum nitrate aqueous solution may be (0.8-1.5) g: 10 mL. The concentration of the second hydrochloric acid may be 0.5-2 mol / L. The usage ratio of the Al-SBA-15, the niobic acid, the second oxalic acid and the water may be (1.5-2.5) g: (0.3-0.6) g: (0.6-0.9) g: 20 mL.
[0056] In the method of the present invention, when the first catalyst contains an active component and a carrier, the active component is an aluminum component, and the carrier is MCM-41, the mass proportion of the active component in the first catalyst is 1.15%-3%. The method may also include preparing the first catalyst according to the following steps: mixing an aqueous solution of tetradecyltrimethylammonium bromide, sodium aluminate, sodium silicate, sulfuric acid and water and stirring at 20-30°C with a stirring rate of 400-800rpm for 2-5h, then reacting at 95-110°C for 5-8 days, separating a solid phase from the obtained mixture by filtration and washing and drying at 100-120°C for 20-30h. The concentration of the aqueous solution of tetradecyltrimethylammonium bromide may be 0.1-0.2g / mL. The concentration of the sulfuric acid may be 8wt%-15wt%. The usage ratio of the tetradecyltrimethylammonium bromide aqueous solution, the sodium aluminate, the sodium silicate, the sulfuric acid and the water can be (90-100) mL: (0.15-0.3) g: (15-20) g: (4-8) g: 15 mL.
[0057] In the method of the present invention, when the first catalyst contains active components, and the active components are zirconium components and aluminum components, the mass ratio of the zirconium component to the aluminum component is 1:(0.14-0.3). The method may also include preparing the first catalyst according to the following steps: mixing F127, hydrochloric acid, aluminum nitrate, zirconium oxychloride and ethanol, stirring at 30-35°C with a stirring rate of 400-800rpm for 20-30h, then hydrothermally treating at 90-110°C for 20-30h, then separating the solid phase by filtration and drying at 50-80°C for 45-60h, and finally calcining at 500-650°C for 4-7h. The concentration of the hydrochloric acid may be 30-38wt%. The amount ratio of the F127, the hydrochloric acid, the aluminum nitrate, the zirconium oxychloride and the ethanol may be (3-4)g:(2-3)g:(2.5-3.5)g:(2-3.5)g:25mL.
[0058] In the method of the present invention, when the first catalyst contains active components, and the active components are tungsten components and aluminum components, the mass ratio of the tungsten component to the aluminum component is 1:(3.82-13.39). The method may also include preparing the first catalyst according to the following steps: mixing the ammonium metatungstate aqueous solution and γ-Al2O3 and stirring at 38-45°C with a stirring rate of 400-800rpm for 15-20h, then separating the solid phase by filtration, and then drying at 100-120°C for 10-15h and calcining at 420-500°C for 4-7h. The concentration of the ammonium metatungstate aqueous solution may be 8-15g / L. The amount ratio of the ammonium metatungstate aqueous solution and the γ-Al2O3 may be 10mL:(0.8-1.5)g.
[0059] In the method described in the present invention, in order to improve the plastic conversion rate and gasoline yield, the second catalyst is preferably at least one of β molecular sieve, Mordenite molecular sieve, MCM-22 molecular sieve and HZSM-5 molecular sieve, more preferably HZSM-5 molecular sieve.
[0060] In the method of the present invention, in order to ensure the occurrence of catalytic cracking reaction, the inert atmosphere is preferably argon and / or nitrogen, more preferably argon. Preferably, the purity of the argon is 99.0wt%-99.9wt%.
[0061] In the method of the present invention, the conditions of the catalytic cracking reaction include: the temperature can be 220-280°C, preferably 230-250°C; the time can be 1-48h, preferably 36-48h. The catalytic cracking reaction can be carried out in a tank reactor.
[0062] In the method described in the present invention, the method may specifically include: mixing the first catalyst and the second catalyst, then mixing and grinding with the polyolefin plastic, and then placing the obtained mixture in the autoclave reactor, introducing an inert atmosphere, heating to 220-280°C and performing the catalytic cracking reaction for 1-48 hours.
[0063] In some embodiments, the method for preparing gasoline using plastics of the present invention comprises: mixing a first catalyst and a second catalyst, then mixing and grinding with a polyolefin plastic, and then placing the obtained mixture in the autoclave reactor, introducing an inert atmosphere, heating to 220-280° C. and performing the catalytic cracking reaction for 1-48 hours, wherein the first catalyst contains an active component and a carrier, the active component is at least one of a tungsten component, a zirconium component, an aluminum component and a niobium component, the carrier is at least one of KIT-6, MCM-41 and SBA-15, and the mass proportion of the active component in the first catalyst is 1.15%-62.59%; the second catalyst is at least one of a β molecular sieve, a Mordenite molecular sieve, an MCM-22 molecular sieve and a HZSM-5 molecular sieve; the ratio of the average pore size of the first catalyst to the second catalyst is (1.75-3.2):1, the average pore size of the first catalyst is 4.2-7.7 nm, and the specific surface area is 460-700 m 2 / g; the average pore size of the second catalyst is 2.0-2.4nm, and the specific surface area is 180-530m 2 / g; the mass ratio of the first catalyst to the second catalyst is 1:(0.25-4); the mass ratio of the total mass of the first catalyst and the second catalyst to the mass of the polyolefin plastic is (0.1-1):1.
[0064] In other embodiments, the method for preparing gasoline using plastics of the present invention comprises: mixing a tungsten source, a zirconium source, a silicon source, a template, hydrochloric acid, n-butanol and water and stirring at 20-30° C. at a stirring rate of 400-800 rpm for 20-30 hours, then performing a hydrothermal reaction at 90-110° C. for 20-30 hours to obtain a mixture, separating a solid phase from the mixture by filtering and washing and drying at 100-120° C. for 20-30 hours, then calcining at 550-750° C. for 5-8 hours to obtain a first catalyst, mixing the first catalyst with a second catalyst, then mixing and grinding with a polyolefin plastic, and then placing the obtained mixture in the autoclave; A reactor is introduced into an inert atmosphere, heated to 220-280° C. and subjected to the catalytic cracking reaction for 1-48 hours, wherein the ratio of the amount of the tungsten source, the zirconium source, the silicon source, the template, the hydrochloric acid, the n-butanol and the water is (0.2-1.8) g: (0.4-1.8) g: (6-10) g: (3.5-4) g: (5-8) g: (3.5-4) g: 130 mL, the second catalyst is HZSM-5 molecular sieve, the ratio of the average pore size of the first catalyst to the second catalyst is (1.75-3.2): 1, the average pore size of the first catalyst is 4.2-7.7 nm, and the specific surface area is 460-700 m2 / g; the average pore size of the second catalyst is 2.0-2.4nm, and the specific surface area is 180-530m 2 / g; the mass ratio of the first catalyst to the second catalyst is 1:(0.25-4); the mass ratio of the total mass of the first catalyst and the second catalyst to the mass of the polyolefin plastic is (0.1-1):1.
[0065] The method for preparing gasoline from plastics of the present invention is further described below by way of examples. The examples are implemented based on the technical solution of the present invention, and detailed implementation methods and specific operation processes are given, but the protection scope of the present invention is not limited to the following examples.
[0066] The experimental methods in the following examples are conventional methods in the art unless otherwise specified. The experimental materials used in the following examples are all commercially available unless otherwise specified. Polyethylene plastic was purchased from Macklin, with a weight average molecular weight of 80,000; polypropylene plastic was purchased from Ruixiang Plastics Company, with a weight average molecular weight of 80,000; HZSM-5 molecular sieve was purchased from Tianjin Nanhua Catalyst Co., Ltd.; the molar ratio of silicon dioxide to aluminum oxide was 25; β molecular sieve, Mordenite molecular sieve and MCM-22 molecular sieve were all purchased from Tianjin Nanhua Catalyst Co., Ltd.
[0067] Example 1
[0068] 0.9 g of ammonium metatungstate, 0.8 g of zirconium oxychloride, 8 g of ethyl silicate, 3.7 g of P123, 6 g of hydrochloric acid with a concentration of 37 wt%, and 3.7 g of n-butanol were added to a conical flask containing 130 mL of deionized water, mixed and stirred at 25 ° C with a stirring rate of 600 rpm for 24 hours, followed by a hydrothermal reaction at 100 ° C for 24 hours to obtain a mixture, and the solid phase was separated from the mixture by filtration and washed and dried at 110 ° C for 24 hours, and then calcined at 550 ° C for 5 hours to obtain WZr-KIT-6 (the active components are tungsten component and zirconium component, the carrier is KIT-6, the mass ratio of the active component in WZr-KIT-6 is 32%, and the mass ratio of the tungsten component to the zirconium component is 1:0.5), 0.02 g of WZr-KIT-6 and 0.08 g of The mixture was mixed with HZSM-5 molecular sieve, and then mixed with 0.3g polyethylene plastic and ground. The obtained mixture was then placed in a kettle reactor, introduced with argon, heated to 240°C and subjected to the catalytic cracking reaction for 48h. After the reaction was completed, the mixture was naturally cooled to 25°C.
[0069] Example 2
[0070] 0.4 g of ammonium metatungstate, 0.4 g of zirconium oxychloride, 6 g of ethyl silicate, 3.5 g of P123, 5 g of hydrochloric acid with a concentration of 30 wt%, and 3.5 g of n-butanol were added to a conical flask containing 130 mL of deionized water, mixed and stirred at 20 ° C with a stirring rate of 400 rpm for 20 hours, followed by a hydrothermal reaction at 90 ° C for 20 hours to obtain a mixture, and the solid phase was separated from the mixture by filtration and washed and dried at 100 ° C for 20 hours, and then calcined at 550 ° C for 5 hours to obtain WZr-KIT-6 (the active components are tungsten component and zirconium component, the carrier is KIT-6, the mass ratio of the active component in WZr-KIT-6 is 21%, and the mass ratio of the tungsten component to the zirconium component is 1:0.52), 0.05 g of WZr-KIT-6 and 0.05 g of The mixture was mixed with HZSM-5 molecular sieve, and then mixed with 0.4 g polyethylene plastic and ground. The obtained mixture was then placed in a kettle reactor, introduced with argon, heated to 220° C. and subjected to the catalytic cracking reaction for 24 h. After the reaction was completed, the mixture was naturally cooled to 25° C.
[0071] Example 3
[0072] 1.8 g of ammonium metatungstate, 1.8 g of zirconium sulfate, 10 g of ethyl silicate, 4 g of P123, 8 g of hydrochloric acid with a concentration of 38 w%, and 4 g of n-butanol were added to a conical flask containing 130 mL of deionized water, mixed and stirred at 30 ° C with a stirring rate of 800 rpm for 30 hours, followed by a hydrothermal reaction at 110 ° C for 30 hours to obtain a mixture, and the solid phase was separated from the mixture by filtration and washed and dried at 120 ° C for 30 hours, and then calcined at 750 ° C for 8 hours to obtain WZr-KIT-6 (the active components are tungsten component and zirconium component, the carrier is KIT-6, the mass ratio of the active component in WZr-KIT-6 is 39%, and the mass ratio of the tungsten component to the zirconium component is 1:0.4), 0.08 g of WZr-KIT-6 and 0.02 g of The HZSM-5 molecular sieve was mixed, and then mixed with 0.1 g of polyethylene plastic and ground. The obtained mixture was then placed in a kettle reactor, introduced with argon, heated to 240° C. and subjected to the catalytic cracking reaction for 1 hour. After the reaction was completed, it was naturally cooled to 25° C.
[0073] Example 4
[0074] 0.2 g of tungsten chloride, 0.8 g of zirconium chloride, 8 g of methyl silicate, 3.7 g of F127, 6 g of 37 wt% hydrochloric acid, and 3.7 g of n-butanol were added to a conical flask containing 130 mL of deionized water, mixed and stirred at 25 ° C with a stirring rate of 600 rpm for 24 hours, followed by a hydrothermal reaction at 100 ° C for 24 hours to obtain a mixture, and the solid phase was separated from the mixture by filtration and washed and dried at 110 ° C for 24 hours, and then calcined at 550 ° C for 6 hours to obtain WZr-KIT-6 (the active components are tungsten component and zirconium component, the carrier is KIT-6, the mass ratio of active components in WZr-KIT-6 is 11%, and the mass ratio of the tungsten component to the zirconium component is 1:3.6), 0.02 g of WZr-KIT-6 and 0.08 g of The HZSM-5 molecular sieve was mixed, and then mixed with 1g of polypropylene plastic and ground. The obtained mixture was then placed in a kettle reactor, argon was introduced, the temperature was raised to 280°C, and the catalytic cracking reaction was carried out for 48h. After the reaction was completed, it was naturally cooled to 25°C.
[0075] Example 5
[0076] 0.9 g of ammonium metatungstate, 8 g of ethyl silicate, 3.7 g of P123, 6 g of hydrochloric acid with a concentration of 37 wt%, and 3.7 g of n-butanol were added to a conical flask containing 130 mL of deionized water, mixed and stirred at 25 ° C with a stirring rate of 600 rpm for 24 h, followed by a hydrothermal reaction at 100 ° C for 24 h to obtain a mixture, and the solid phase was separated from the mixture by filtration and washed and dried at 110 ° C for 24 h, and then calcined at 550 ° C for 7 h to obtain W-KIT-6 (the active component is the tungsten component, the carrier is KIT-6, and the mass proportion of the active component in W-KIT-6 is 22%), 0.025 g of W-KIT-6 and 0.075 g of The mixture was mixed with HZSM-5 molecular sieve, and then mixed with 0.3g polyethylene plastic and ground. The obtained mixture was then placed in a kettle reactor, introduced with argon, heated to 240°C and subjected to the catalytic cracking reaction for 48h. After the reaction was completed, the mixture was naturally cooled to 25°C.
[0077] Example 6
[0078] 0.9 g zirconium oxychloride, 8 g ethyl silicate, 3.7 g P123, 6 g hydrochloric acid with a concentration of 37 wt%, and 3.7 g n-butanol were added to a conical flask containing 130 mL of deionized water, mixed and stirred at 25 ° C with a stirring rate of 600 rpm for 24 hours, followed by a hydrothermal reaction at 100 ° C for 24 hours to obtain a mixture, and the solid phase was separated from the mixture by filtration and washed and dried at 110 ° C for 24 hours, and then calcined at 550 ° C for 5 hours to obtain Zr-KIT-6 (the active component is the zirconium component, the carrier is KIT-6, and the mass proportion of the active component in Zr-KIT-6 is 13%), 0.02 g Zr-KIT-6 and 0.08 g The mixture was mixed with HZSM-5 molecular sieve, and then mixed with 0.3g polyethylene plastic and ground. The obtained mixture was then placed in a kettle reactor, introduced with argon, heated to 240°C and subjected to the catalytic cracking reaction for 48h. After the reaction was completed, the mixture was naturally cooled to 25°C.
[0079] Example 7
[0080] 2.2 g P123 and 1.2 g oxalic acid were added to 40 mL hydrochloric acid solution with a concentration of 2 mol / L, and then 4.58 g ethyl silicate was added and mixed, and stirred at 25 ° C at a stirring rate of 600 rpm for 24 hours to obtain SBA-15, and then 1 g SBA-15 was placed in 10 ml of 2 mol / L aluminum nitrate aqueous solution, and the pH was adjusted to 2 by hydrochloric acid with a concentration of 1 mol / L, and then placed in a closed autoclave, and hydrothermally reacted at 120 ° C for 24 hours, and the solid phase was separated from the obtained mixture by filtration and washed and dried at 100 ° C for 24 hours to obtain Al-SBA-15 (the active component is the aluminum component, the carrier is SBA-15, and the mass proportion of the active component in Al-SBA-15 is 54%), 0.02 g Al-SBA-15 and 0.08 g The mixture was mixed with HZSM-5 molecular sieve, and then mixed with 0.3g polyethylene plastic and ground. The obtained mixture was then placed in a kettle reactor, introduced with argon, heated to 240°C and subjected to the catalytic cracking reaction for 48h. After the reaction was completed, the mixture was naturally cooled to 25°C.
[0081] Example 8
[0082] 2.2 g P123 and 1.2 g oxalic acid were added to 40 mL hydrochloric acid solution with a concentration of 2 mol / L, and then 4.58 g ethyl silicate was added and mixed, and stirred at 25 ° C with a stirring rate of 600 rpm for 24 h to obtain SBA-15, and then 1 g SBA-15 was placed in 10 ml of 2 mol / L aluminum nitrate aqueous solution, and the pH was adjusted to 2 by 1 mol / L hydrochloric acid, and then placed in a closed autoclave, and hydrothermally reacted at 120 ° C for 24 h, and the solid phase was separated from the obtained mixture by filtration and washed and dried at 100 ° C for 24 h to obtain Al-SBA-15, and 1 g SBA-15 was placed in 10 ml of 2 mol / L aluminum nitrate aqueous solution, and the pH was adjusted to 2 by 1 mol / L hydrochloric acid, and then placed in a closed autoclave, and hydrothermally reacted at 120 ° C for 24 h, and the solid phase was separated from the obtained mixture by filtration and washed and dried at 100 ° C for 24 h to obtain Al-SBA-15, and 1 g Al-SBA-15, 0.2 g of niobic acid, a second 0.36 g of oxalic acid and 20 mL of water were mixed and stirred at 25 ° C at a stirring rate of 600 rpm for 16 h, the solid phase was separated from the obtained mixture by filtration and washed and dried at 100 ° C for 24 h, and then calcined at 450 ° C for 5 h to obtain Nb-Al-SBA-15 (the active components are niobium component and aluminum component, the carrier is SBA-15, the mass proportion of active components in Nb-Al-SBA-15 is 61%, and the mass ratio of the niobium component to the aluminum component is 1:7.7), 0.02 g of Nb-Al-SBA-15 and 0.08 g of HZSM-5 molecular sieve were mixed, and then mixed with 0.3 g of polyethylene plastic and ground, and then the obtained mixture was placed in an autoclave reactor, argon was introduced, the temperature was raised to 240 ° C and the catalytic cracking reaction was carried out for 48 hours, and the reaction was naturally cooled to 25 ° C after the reaction was completed.
[0083] Example 9
[0084] 95 mL of 0.158 g / mL tetradecyltrimethylammonium bromide aqueous solution, 2.1 g of sodium aluminate, 18.7 g of sodium silicate, 5.6 g of 10 wt% sulfuric acid and 15 mL of water were mixed and stirred at 25°C at a stirring rate of 600 rpm for 3 h, followed by reaction at 100°C for 6 days, the solid phase was separated from the obtained mixture by filtration and washed and dried at 100°C for 24 h to obtain Al-MCM-41 (the active component is the aluminum component, the carrier is MCM-41, and the mass proportion of the active component in Al-MCM-41 is 3%), 0.02 g of Al-MCM-41 and 0.08 g of HZSM-5 molecular sieve were mixed, and then mixed with 0.3 g of polyethylene plastic and ground, and then the obtained mixture was placed in an autoclave reactor, argon was introduced, the temperature was raised to 240°C and the catalytic cracking reaction was carried out for 48 h, and the reaction was naturally cooled to 25°C after the reaction was completed.
[0085] Example 10
[0086] The method of Example 1 was followed, except that the HZSM-5 molecular sieve was replaced by β molecular sieve.
[0087] Embodiment 11
[0088] The method of Example 1 was followed, except that the HZSM-5 molecular sieve was replaced by Mordenite molecular sieve.
[0089] Example 12
[0090] The method of Example 1 was followed, except that the HZSM-5 molecular sieve was replaced by an MCM-22 molecular sieve.
[0091] Embodiment 13
[0092] The method of Example 1 was followed, except that the polyethylene plastic was replaced with recycled powder of polyolefin plastic (the gloves and plastic bags made of PE material were dried at 80° C. and then ground).
[0093] Embodiment 14
[0094] The method of Example 1 was followed, except that 0.02 g of WZr-KIT-6 and 0.08 g of HZSM-5 molecular sieve were replaced with 0.005 g of WZr-KIT-6 and 0.095 g of HZSM-5 molecular sieve.
[0095] Embodiment 15
[0096] 3.2g F127, 2g hydrochloric acid with a concentration of 37wt%, 3g aluminum nitrate and 2.6g zirconium oxychloride are added to 25mL anhydrous ethanol, stirred at 32°C with a stirring rate of 600rpm for 24h, the mixed solvent is placed in a hydrothermal autoclave and hydrothermally treated at 100°C for 24h, then the solid phase is separated by filtration and dried in an oven at 60°C for 48h, and then calcined at 550°C for 5h to obtain ZrO2-Al2O3; 0.02g ZrO2-Al2O3 (the mass ratio of zirconium component to aluminum component is 1:0.29) and 0.08g HZSM-5 molecular sieve are mixed, and then mixed with 0.3g polyethylene plastic and ground, and then the obtained mixture is placed in an autoclave reactor, argon is introduced, the temperature is raised to 240°C and the catalytic cracking reaction is carried out for 48h, and the reaction is naturally cooled to 25°C after the reaction is completed.
[0097] Example 16
[0098] 0.1g of ammonium metatungstate was dissolved in 10mL of deionized water, and 1g of γ-Al2O3 was added. The obtained mixture was stirred at 40°C with a stirring rate of 600rpm for 16h, and then the solid phase was separated by filtration, and then dried at 110°C for 12h and calcined at 450°C for 5h to obtain WO3-Al2O3; 0.02g of WO3-Al2O3 (the mass ratio of tungsten component to aluminum component was 1:7.16) was mixed with 0.08g of HZSM-5 molecular sieve, and then mixed with 0.3g of polyethylene plastic and ground, and then the obtained mixture was placed in a kettle reactor, argon was introduced, the temperature was raised to 240°C and the catalytic cracking reaction was carried out for 48h, and the reaction was naturally cooled to 25°C after completion.
[0099] Comparative Example 1
[0100] The method of Example 1 was followed, except that 0.02 g WZr-KIT-6 and 0.08 g HZSM-5 molecular sieve were replaced with 0.095 g WZr-KIT-6 and 0.005 g HZSM-5 molecular sieve.
[0101] Comparative Example 2
[0102] The method of Example 1 was followed, except that WZr-KIT-6 was not added, as follows:
[0103] 0.1 g of HZSM-5 molecular sieve was mixed, and then mixed with 0.3 g of polyethylene plastic and ground. The obtained mixture was then placed in a kettle reactor, introduced with argon, heated to 240° C., and subjected to the catalytic cracking reaction for 48 hours. After the reaction was completed, the mixture was naturally cooled to 25° C.
[0104] Comparative Example 3
[0105] The method of Example 1 was followed, except that no HZSM-5 molecular sieve was added, as follows:
[0106] 0.1 g of WZr-KIT-6 was mixed, and then mixed with 0.3 g of polyethylene plastic and ground. The obtained mixture was then placed in a kettle reactor, introduced with argon, heated to 240° C., and subjected to the catalytic cracking reaction for 48 h. After the reaction was completed, the mixture was naturally cooled to 25° C.
[0107] Test Example 1
[0108] The WZr-KIT-6 and HZSM-5 prepared in Example 1 were characterized by transmission electron microscopy. The test method was based on the national standard GB / T 17507. Figure 1 and Figure 2 As shown, it can be seen that the WZr-KIT-6 material has an obvious mesoporous structure, and the HZSM-5 molecular sieve is a microporous material.
[0109] The WZr-KIT-6, HZSM-5 and the mixture of WZr-KIT-6 and HZSM-5 prepared in Example 1 were characterized by XRD using an X-ray diffractometer. The test method was based on the national standard GB / T30904-2014. Figure 3 As shown, it can be seen that the tungsten component and the zirconium component are highly dispersed on the KIT-6 carrier, and the crystal structure of HZSM-5 is not changed after WZr-KIT-6 is mixed with the HZSM-5 molecular sieve catalyst.
[0110] The WZr-KIT-6, HZSM-5 and the mixture of WZr-KIT-6 and HZSM-5 prepared in Example 1 were subjected to low-temperature nitrogen adsorption and desorption tests. The test method was based on the national standard GB / T 5211-2008. Figure 4 As shown, it can be seen that WZr-KIT-6 is a mesoporous material and HZSM-5 molecular sieve is a microporous material. The average pore size and specific surface area of WZr-KIT-6 and HZSM-5 are recorded in Table 1.
[0111] The WZr-KIT-6, HZSM-5 and the mixture of WZr-KIT-6 and HZSM-5 prepared in Example 1 were subjected to ammonia TPD test. Before adsorption, 100 mg of the sample was activated in flowing helium at 300°C for 2 h, followed by ammonia adsorption for 30 min at 100°C and helium purge for 1 h. Finally, the temperature was increased from 100°C to 700°C at a rate of 10°C / min and the TCD signal was recorded, as shown in FIG. Figure 5 As shown, it can be seen that the mixed catalyst has fewer strong acid sites compared with the HZSM-5 molecular sieve.
[0112] The catalysts prepared in Examples 2-16 were also subjected to transmission electron microscopy characterization, XRD characterization, low-temperature nitrogen adsorption and desorption test, and ammonia TPD test. The results were similar to those in Example 1 and are not repeated here. The measured average pore size and specific surface area of the catalysts are recorded in Table 1.
[0113] Test Example 2
[0114] The gaseous products after the reaction of Examples 1-16 and Comparative Examples 1-3 were respectively collected by air bags for qualitative and quantitative analysis by gas chromatography. At the same time, 2 mL of dichloromethane was added to the autoclave reactor, and then centrifuged at a speed of 10000 rpm for solid-liquid separation. The separated liquid products were subjected to qualitative and quantitative testing by gas chromatography-mass spectrometry and gas chromatography. The testing method referred to the national standard GB / T 30431-2020. The separated solid products were dried at 120°C for 12 h. The plastic conversion rate and gasoline yield were calculated and recorded in Table 2. The calculation formula is: Plastic conversion rate = ((initial plastic mass - remaining plastic mass) / initial plastic mass), gasoline yield = (gasoline mass / (initial plastic mass - remaining plastic mass)).
[0115] Stability test
[0116] The WZr-KIT-6 and HZSM-5 molecular sieves prepared in Example 1 were mixed, and then mixed with 0.3g of polyethylene plastic and ground. The obtained mixture was then placed in a tank reactor, argon was introduced, the temperature was raised to 240°C, and the catalytic cracking reaction was carried out for 12 hours. After the reaction, it was naturally cooled to 25°C. The gas products after the reaction were collected by air bags for qualitative and quantitative analysis by gas chromatography. At the same time, 2mL of dichloromethane was added to the tank reactor, and then the liquid was taken out and centrifuged at a speed of 10000rpm for solid-liquid separation. The separated liquid product was subjected to qualitative and quantitative testing by gas chromatography-mass spectrometry and gas chromatography. The test method was based on the national standard GB / T 30431-2020. The separated solid product was dried at 120°C for 12 hours, and the plastic conversion rate was calculated. After the solid product separated each time was calcined at 550°C for 5 hours, the above operation was repeated for catalytic cracking of polyethylene plastic 4 times, and the plastic conversion rate was recorded. Figure 6 .
[0117] from Figure 6 It can be seen that according to the method for preparing gasoline from plastics of the present invention, the catalyst can still maintain its initial performance after multiple reactions, recycling and regeneration.
[0118] Herein, the active component content in the catalyst in Examples 1-16 was measured by inductively coupled plasma (ICP) testing, and the testing method was based on the national standard GB / T 13747.26-2022.
[0119] Table 1
[0120] catalyst Average pore size (nm) <![CDATA[Specific surface area (m 2 / g)]]> WZr-KIT-6 in Example 1 4.6 460 WZr-KIT-6 in Example 2 5.0 480 WZr-KIT-6 in Example 3 5.4 490 WZr-KIT-6 in Example 4 7.7 500 W-KIT-6 in Example 5 5.8 540 Zr-KIT-6 in Example 6 4.2 670 Al-SBA-15 in Example 7 5.6 700 Nb-Al-SBA-15 in Example 8 5.8 680 Al-MCM-41 in Example 9 6.0 650 HZSM-5 molecular sieve 2.4 350 Beta molecular sieve 2.2 530 Mordenite Molecular Sieve 2.2 440 MCM-22 molecular sieve 2.3 490 <![CDATA[ZrO2 - Al2O3 in Example 15]]> 4.6 130 <![CDATA[WO3 - Al2O3 in Example 16]]> 4.7 200
[0121] Table 2
[0122] serial number Gasoline yield (%) Plastic conversion rate (%) Example 1 88.0 95.2 Example 2 60.7 69.8 Example 3 56.0 63.0 Example 4 69.8 76.1 Example 5 70.2 78.6 Example 6 72.0 79.6 Example 7 59.8 70.4 Example 8 60.2 71.0 Example 9 59.8 65.0 Example 10 77.2 87.8 Embodiment 11 57.8 68.0 Example 12 56.4 69.1 Embodiment 13 82.2 90.0 Embodiment 14 85.7 96.5 Embodiment 15 50.5 60.4 Example 16 45.0 54.0
[0123] It can be seen from the results in Table 2 that Examples 1-16 using the method for preparing gasoline from plastics of the present invention have higher gasoline yields and plastic conversion rates.
[0124] The preferred embodiments of the present invention are described in detail above, but the present invention is not limited thereto. Within the technical concept of the present invention, the technical solution of the present invention can be subjected to a variety of simple modifications, including the combination of various technical features in any other suitable manner, and these simple modifications and combinations should also be regarded as the contents disclosed by the present invention and belong to the protection scope of the present invention.
Claims
1. A method for preparing gasoline using plastic, characterized in that: The method comprises: in an inert atmosphere, subjecting polyolefin plastic to a catalytic cracking reaction under the action of a first catalyst and a second catalyst, Wherein, the first catalyst contains an active component and an optional carrier, the active component is at least one of a tungsten component, a zirconium component, an aluminum component and a niobium component, and the carrier is a mesoporous molecular sieve; The second catalyst is a microporous silicon-aluminum molecular sieve; The mass ratio of the first catalyst to the second catalyst is 1:(0.25-20).
2. The method according to claim 1, characterized in that The mass ratio of the first catalyst to the second catalyst is 1:(0.25-4).
3. The method according to claim 1 or 2, characterized in that: The mass ratio of the total mass of the first catalyst and the second catalyst to the amount of the polyolefin plastic used is (0.1-1):
1.
4. The method according to any one of claims 1 to 3, characterized in that: The polyolefin plastic is polyethylene plastic and / or polypropylene plastic.
5. The method according to any one of claims 1 to 3, characterized in that: The ratio of the average pore diameter of the first catalyst to that of the second catalyst is (1.75-3.2):
1.
6. The method according to claim 1 or 5, characterized in that: In the first catalyst, the mesoporous molecular sieve is at least one of KIT-6, MCM-41 and SBA-15; and / or The first catalyst contains an active component and a carrier, and the mass proportion of the active component in the first catalyst is 1.15%-62.59%.
7. The method according to any one of claims 1 to 6, characterized in that: The first catalyst contains an active component and a carrier, the active component is a tungsten component and a zirconium component, and the carrier is KIT-6; Preferably, the mass proportion of the active component in the first catalyst is 8.3%-51.62%, preferably 11%-39%, more preferably 16%-32%; Preferably, the mass ratio of the tungsten component to the zirconium component is 1:(0.08-4).
8. The method according to claim 7, characterized in that The method further comprises preparing the first catalyst by the following steps: mixing and stirring a tungsten source, a zirconium source, a silicon source, a template, hydrochloric acid, n-butanol and water, followed by a hydrothermal reaction to obtain a mixture, separating a solid phase from the mixture and calcining the mixture; Preferably, the tungsten source is ammonium metatungstate and / or tungsten chloride; Preferably, the zirconium source is at least one of zirconium oxychloride, zirconium chloride, zirconium nitrate and zirconium sulfate; Preferably, the silicon source is ethyl silicate and / or methyl silicate; Preferably, the template is P123 and / or F127; Preferably, the ratio of the amount of the tungsten source, the zirconium source, the silicon source, the template, the hydrochloric acid, the n-butanol and the water is (0.2-1.8) g: (0.4-1.8) g: (6-10) g: (3.5-4) g: (5-8) g: (3.5-4) g: 130 mL; Preferably, the concentration of the hydrochloric acid is 30wt%-38wt%; Preferably, the conditions of the hydrothermal reaction include: temperature of 90-110°C and time of 20-30h; Preferably, the calcination conditions include: temperature of 550-750° C. and time of 5-8 h.
9. The method according to any one of claims 1 to 5, characterized in that: The second catalyst is at least one of β molecular sieve, Mordenite molecular sieve, MCM-22 molecular sieve and HZSM-5 molecular sieve, preferably HZSM-5 molecular sieve.
10. The method according to any one of claims 1 to 9, characterized in that: The conditions of the catalytic cracking reaction include: temperature of 220-280°C and time of 1-48h; Preferably, the catalytic cracking reaction is carried out in a tank reactor.